2017
DOI: 10.7448/ias.20.1.21771
|View full text |Cite
|
Sign up to set email alerts
|

HIV, violence, blame and shame: pathways of risk to internalized HIV stigma among South African adolescents living with HIV

Abstract: Introduction: Internalized HIV stigma is a key risk factor for negative outcomes amongst adolescents living with HIV (ALHIV), including non-adherence to anti-retroviral treatment, loss-to-follow-up and morbidity. This study tested a theoretical model of multi-level risk pathways to internalized HIV stigma among South African ALHIV.Methods: From 2013 to 2015, a survey using total population sampling of ALHIV who had ever initiated anti-retroviral treatment (ART) in 53 public health facilities in the Eastern Cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
96
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 56 publications
12
96
0
Order By: Relevance
“…Discrimination refers to overt instances of being treated differently from others due to a person’s HIV status [7]. Adolescents living with HIV are subjected to discrimination within their communities and families both because of their own HIV status and, sometimes, because of their caregivers’ HIV status [8‐10]. Adolescents living with HIV also report frequent instances of healthcare providers getting angry and shouting at them, which they experience as discrimination [3].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Discrimination refers to overt instances of being treated differently from others due to a person’s HIV status [7]. Adolescents living with HIV are subjected to discrimination within their communities and families both because of their own HIV status and, sometimes, because of their caregivers’ HIV status [8‐10]. Adolescents living with HIV also report frequent instances of healthcare providers getting angry and shouting at them, which they experience as discrimination [3].…”
Section: Introductionmentioning
confidence: 99%
“…Being a target of discrimination can lead to internalized stigma [11], which occurs when adolescents internalize stigmatizing characterizations of people living HIV and accept them as applicable to themselves [12]. Internalized stigma evokes feelings of shame, guilt, helplessness and, in some cases, suicidal ideation [10,13‐16]. A national survey of more than 10,000 people living with HIV in South Africa found that 36% reported experiencing discrimination and 43% reported experiencing internalized HIV stigma in the past year.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations